CRAFTING AN EFFECTIVE METHODS SECTION IN IMRAD STRUCTURE: PRINCIPLES, TECHNIQUES, AND ACADEMIC STANDARDS - Rustamova Adash Eshankulovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: The Methods section is one of the most essential components of scientific writing because it explains how research was conducted and ensures transparency, reliability, and reproducibility of scholarly investigations. Within the IMRAD structure—Introduction, Methods, Results, and Discussion—the Methods section serves as the methodological foundation of academic research and allows readers to evaluate the validity and credibility of a study. This article examines the principles, structure, and techniques of writing an effective Methods section in IMRAD style. The study explores qualitative, quantitative, and mixed-methods research designs, data collection procedures, sampling strategies, ethical considerations, and statistical analysis techniques commonly presented in academic writing. Furthermore, the article analyzes language conventions, citation practices, methodological transparency, and common challenges encountered by researchers when composing Methods sections. The findings suggest that a clearly organized and methodologically sound Methods section significantly strengthens research quality, academic integrity, and scientific reproducibility. The article concludes that mastering IMRAD methodological writing is essential for researchers seeking successful publication in international academic journals.
Keywords: Keywords: IMRAD structure, Methods section, academic writing, research methodology